A relação com o saber na mentoria de diretores escolares: considerações a partir de uma formação prática - Oliveira, Ricardo Gavioli de (2023)
The present research originated from reflections on some questions that originated this thesis: does the exchange of experience between principals enable the construction of the relationship with the Knowledge (Charlot, 2000) about school management? Can a mentoring of directors or not promote the rupture of training models traditionally offered to this public? With this problem, the general objective of this study emerged, to understand the relationship with knowledge submitted to the practice of school management, from the identification of the knowledge and learning that the mentoring principals and mentees said they had produced, due to the practical training in mentoring of principals. And, the specific objectives: to ascertain what mobilized the directors in relation to the desire to learn and; elucidate how the activities developed during Mentoring in Practice contributed to instigate ruptures in relation to the instrumental perspective that prevails in the guidelines directed to this audience. The theoretical framework was based on Bernard Charlot's analytical propositions about the Relationship with Knowledge (RcS). Of a qualitative nature, we sought to understand the relationship with knowledge submitted to the practice of school management, based on the identification of the knowledge and learning that principals said they had produced, as a result of training. The empirical part of the research consisted of conducting two focus groups as methodological instruments for data collection: one with mentoring directors and the other with mentored directors, belonging to the five Brazilian regions that were part of the training in Mentoring in Practice, which took place between August 2021 and June 2022. This training was developed by the Study and Research Group on Education, Subjectivity and Culture (GEPESC) of the Federal University of São Carlos (UFSCar), in partnership with the Secretariat of Basic Education of the Ministry of Education (SEB/MEC). The data showed two constellations of analysis: 1) Mutual learning relationship between principals, mentors and mentees and 2) Contributions of mentoring to coping with challenges in the school. The results revealed that the relationship with knowledge submitted to school management demands from principals a complex mediation process, in view of the need to mobilize the community in favor of the development of collaborative activities that favor the organization of the school, expanding its degree of autonomy and enabling the democratization of its management. The identification of the knowledge learned by the principals revealed new professional strategies to cope with challenges and problems identified in the school routine, contributing to minimize the feeling of isolation and insecurity through the exercise of the function. This was only possible due to the training methodology of Mentoring in Practice, which instigated the establishment of a new relationship between these directors, from which they were able to carry out the systematized exchange of knowledge and experiences among peers, which favored the rupture with the merely technical and bureaucratizing logic of guidance traditionally directed to this audience.